Perspectives for TNF-α-targeting therapies - Lorenz, Hanns-Martin (BioMed Central, 2002)
CHAPTER SUMMARY: Rheumatoid arthritis (RA) is the most common chronic autoimmunopathy, clinically leading to joint destruction as a consequence of the chronic inflammatory processes. The pathogenesis of this disabling disease is not well understood, but molecular events leading to tissue inflammation with cartilage and bone destruction are now better defined. Therapy with slow-acting, disease-modifying antirheumatic drugs (DMARDs), such as low-dose methotrexate, which is generally accepted as a standard, leads to a significant amelioration of symptoms but does not stop joint destruction. Due to these disappointing treatment options and the identification of certain inflammatory mediators as therapeutic targets, novel therapeutic agents such as monoclonal antibodies, cytokine-receptor/human-immunoglobulin constructs or recombinant human proteins have been tested in RA with some success. Clinical trials testing anti-TNF-α agents, alone or in combination with methotrexate, have convincingly shown the feasibility and efficacy of these novel approaches to the therapy of RA. A clinical trial testing combination therapy with chimeric (mouse/human) anti-TNF-α monoclonal antibody infliximab and methotrexate showed, for the first time in any RA trial, that there was no median radiological progression in the groups given infliximab plus methotrexate over a 12-month observation period. Similar encouraging results might arise from trials employing other TNF-α-directed agents, such as the fully human monoclonal antibody D2E7, the p75 TNF-α-receptor/Ig construct, etanercept, or others, as discussed in this review. Combination partners other than methotrexate will be established as suitable cotreatment along with anti-TNF-α biologicals. Forthcoming new indications for TNF-α-targeted therapies are discussed.